FLOOD HAZARDS, VULNERABILITY AND ADAPTATIONS IN UPPER IMO RIVER BASIN OF SOUTH EASTERN NIGERIA - Ezedike, Cyprian Echefu; Chibo, Christian Nnamdi (African Journal of Social and Behavioural Sciences, 2019)
Imo River Basin has a fluvial erosion system dominated by powerful rivers coming down from steep slopes in the area. This research investigated various hazards associated with flood, the vulnerable areas, elements at risk of flood and various adaptation strategies to cope with the hazards. The study identified the role of elevation, and also elements at risk of flooding. It also examine the effectiveness or otherwise of the adaptation strategies for coping with the hazards. Both primary and secondary data were used for this study and they were generated from field measurement, questionnaire survey, library and websites searches. Other types of data were generated from topographical, geological, and Digital Elevation model (DEM) maps, while the hydro meteorological data was sourced from NIMET, and some higher institutions. Eight hundred copies of questionnaire were distributed using systematic sampling to eight locations used for a pilot survey. 96 percent of the questionnaire were retrieved and used for the study. Thirteen flood events were identified. Their causes, years and dates of events were documented, and the damages done were evaluated. The study established that for each flood event, there is over 200mm of rain observed on the day of the flood and the day before the flood. The study also revealed that the areas that situate at higher elevation are less prone to flood hazards than low elevations. Elements identified to be at risk of flood are agricultural land, residential dwellings, and retail trading and related services. The study thereby recommends non settlement at flood plains and flood prone areas and rearrangement of land use activities in the upper Imo River Basin among others